The globalization of strategy research - Baum, Joel A. C.; Lampel, Joseph (Emerald, 2010)
The field of strategic management emerged and developed in North America before migrating to other parts of the world. Until recently, the relationship between North American strategy research and research elsewhere was asymmetric: North America led, other research communities followed. More recently, however, the interaction between North American strategy researchers and those working in other regions has evolved into a conversation. Oftentimes the conversation is collaborative and productive, but occasionally it is adversarial and provocative. While the globalization of strategy research has added considerably to our understanding, it has also brought about greater theoretical and methodological pluralism as formal, rhetorical, discursive, and practice perspectives (among others) emerge and gain traction within the field. For some, pluralism is a phase in the larger cycle of variation and consolidation that characterizes the evolution of strategy research. For others, it is a reflection of fundamentally different socioeconomic conditions and intellectual traditions around the world that is not only likely to persist, but also to give rise to distinctive and potentially irreconcilable schools of thought. Volume 27 of Advances in Strategic Management brings together various emerging perspectives in strategy research for further interaction and debate. By creating a forum for discussing issues at the interface of emerging perspectives and longstanding traditions, we aim to assemble a compendium that contributes to cross-fertilization among them, as well as a catalyst for future research countering the separatist logic that threatens to partition the field.
Description based on print version record.